Non-invasive electromagnetic detection of prostate cancer: efficiency analysis - M. E. Chaliy; E. V. Afanasyevskaya; A. S. Amirkhanyan; A. A. Strigunov; A. M. Kadysheva; E. V. Kolygina; A. S. Shurygina; A. S. Tivtikyan; A. V. Kadrev; V. K. Dzitiev; D. A. Okhobotov; N. I. Sorokin; et al. (Вестник урологии, 2023)
Introduction. Early diagnosis of cancer is one of the most important international strategies. Malignant and healthy tissues differ in the interaction with electromagnetic waves. Pilot studies show a potential perspective for non-invasive analysis of electromagnetic anisotropy in biological tissues.Objective. To assess the diagnostic importance of the electromagnetic detection of prostate cancer (PCa) within the prospective study.Materials & methods. One hundred and twenty-four patients were included to undergo a prostate biopsy, transurethral prostate resection, or radical prostatectomy. The investigators did not have information on their clinical details. Research technique: the probe was applied to the perineal region, turning it in three planes. A reduction of the 465 MHz band below a threshold was fixed and was considered suspect for PCa. The results of electromagnetic evaluation were compared with the findings of a pathomorphological study after biopsy or surgery.Results. Fourty-seven true-positive and 21 true-negative results were detected, 20 false-negative and 46 false-positive (follow-up group as potentially true-positive group). The overall sensitivity was 82%, specificity – 31%. The positive and negative predictive values were 73% and 62%, respectively. The accuracy of the method was 54%.Conclusion. Early PCa stage could be a reason for many false-positive results and low specificity, as a result. PCa detection is significantly reduced with lesions less than 3 mm, therefore patients with false-positive results were placed in the follow-up group. Patients’ examination with the TRIMprob TM («Galileo Avionica» SpA, Torino, Italy) could increase the early PCa detection at the screening. The research is currently ongoing.